EFEKTIFITAS MEKANISME TRANSMISI KEBIJAKAN MONETER GANDA DI INDONESIA - Anisa Noviasari (Media Ekonomi, 2012)
Indonesia is a country that has dual banking system, conventional banking and Islamic banking. Bank Indonesia as the monetary authority, should conduct monetary policy in conventional and Islamic monetary policy to effectively influence the overall macroeconomic situation. This thesis aims to investigate transmission mechanism of dual monetary system from conventional and Islamic policy rates to inflation using VAR methods. The data used in this research is the Consumer Price Index, total loans conventional bank, total financing Islamic bank, conventional bank lending rates, Rate of Profit Sharing Islamic Banking interbank offered rate data conventional bank, interbank offered profit sharing data, Bank Indonesia Certificate rate convensional bank, Bank Indonesia Certificate profit sharing Islamic bank in Indonesia period 2005:01-2012:11. Results of analysis of this study suggest that the monetary policy to ‘reducing inflation’ with Islamic patterns more effectively than with conventional pattern. In a dual monetary system, an alternative approach to monetary policy can be conducted using a quantitative approach that is not contrary to conventional and Shariah.Keyword: Monetary Transmission Mechanism, The Interest Rate Pass Throught, Conventional Banking, Islamic Banking.